2016
DOI: 10.1080/08982104.2016.1239636
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced skin deposition and delivery of voriconazole using ethosomal preparations

Abstract: Despite its broad-spectrum antifungal properties, voriconazole has many side effects when administered systemically. The aim of this work was to develop an ethosomal topical delivery system for voriconazole and test its potential to enhance the antifungal properties and skin delivery of the drug. Voriconazole was encapsulated into various ethosomal preparations and the effect of phospholipid and ethanol concentrations on the ethosomes properties were evaluated. The ethosomes were evaluated for drug encapsulati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
51
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 75 publications
(55 citation statements)
references
References 42 publications
4
51
0
Order By: Relevance
“…Zhang et al, showed that the transdermal flux and skin deposition of psoralen-loaded ethosomes were 3.5 and 2.15 times higher than those achieved using liposomes, respectively [28]. We also showed that ethosomes had~6-fold higher voriconazole permeation through rat abdominal skin compared with the drug hydroalcoholic solution [29]. These results suggest that ethosomes could be a potentially effective delivery system to increase anthralin efficacy against psoriasis and limit its adverse effects.…”
Section: Introductionsupporting
confidence: 57%
See 2 more Smart Citations
“…Zhang et al, showed that the transdermal flux and skin deposition of psoralen-loaded ethosomes were 3.5 and 2.15 times higher than those achieved using liposomes, respectively [28]. We also showed that ethosomes had~6-fold higher voriconazole permeation through rat abdominal skin compared with the drug hydroalcoholic solution [29]. These results suggest that ethosomes could be a potentially effective delivery system to increase anthralin efficacy against psoriasis and limit its adverse effects.…”
Section: Introductionsupporting
confidence: 57%
“…Anthralin-loaded ethosomes were prepared by the cold method as described previously with some modifications [29,32]. Table 2 shows the different components of ethosomes and their proportions.…”
Section: Preparation Of Anthralin-loaded Ethosomesmentioning
confidence: 99%
See 1 more Smart Citation
“…The drug is supposed to be entrapped in the aqueous compartment of the vesicles, and the decrease in the EE may be attributed to the increase in the fluidity of vesicles upon increase in the ethanol content leading to drug leakage [33]. Vesicle size had direct relationship with PC and negative relation with PG and ethanol these results were in agreement with the reported results [32,34]. The size reduction with increasing PG and ethanol could be attributed to negatively charge by ethanol which causes electrostatic repulsion and some degree of stearic stabilization.…”
Section: Preparation and Study Of The Effect Of Formulation Variablessupporting
confidence: 82%
“…This size is smaller than that obtained by DLS measurements (Table 2), since DLS measurements give the hydrodynamic diameter of the nanoparticles, which is usually larger than the actual particle size. In contrast, TEM measurements give the size of the vesicles after drying [50]. Figure 4 shows the in vitro SP release from various formulations in phosphate-buffered saline pH 7.4.…”
Section: Dsc Studiesmentioning
confidence: 99%